2017
DOI: 10.1037/pro0000116
|View full text |Cite
|
Sign up to set email alerts
|

Race-based traumatic stress, racial identity statuses, and psychological functioning: An exploratory investigation.

Abstract: To understand the impact racial experiences have on people of color, it is important to consider both whether there are any race-based traumatic stress symptoms (RBTS) and within-group psychological differences as reflected in one's racial identity status attitudes (RISA). Moreover, if the combination of RBTS reactions and racial identity status attitudes are related to their psychological functioning? The current study explored the relationships between a person's reactions to memorable racial encounters as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
74
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(76 citation statements)
references
References 29 publications
0
74
2
Order By: Relevance
“…Racism also has devastating effects on the mental health of racialized individuals, raising the risk for depression (Noh & Kaspar, 2003) and anxiety (Graham, West, Martinez, & Roemer, 2016). Scholars have also conceptualized racism as a chronic stressor that has the potential to produce trauma and post-traumatic stress disorder (PTSD; Carter, 2007; Carter et al, 2017). Racism manifests in our built environment and results in disparities with exposure to environmental toxins and pollution; this type of environmental racism, in turn, impacts the health and well-being of POCI communities (Taylor, 2014).…”
Section: The Context Of Racism In the United Statesmentioning
confidence: 99%
“…Racism also has devastating effects on the mental health of racialized individuals, raising the risk for depression (Noh & Kaspar, 2003) and anxiety (Graham, West, Martinez, & Roemer, 2016). Scholars have also conceptualized racism as a chronic stressor that has the potential to produce trauma and post-traumatic stress disorder (PTSD; Carter, 2007; Carter et al, 2017). Racism manifests in our built environment and results in disparities with exposure to environmental toxins and pollution; this type of environmental racism, in turn, impacts the health and well-being of POCI communities (Taylor, 2014).…”
Section: The Context Of Racism In the United Statesmentioning
confidence: 99%
“…The impact of negative race‐based incidents on a person's psychological functioning has been widely researched for people of color (Carter, Johnson, et al, 2017; English, Lambert, & Ialongo, 2014). However, researchers have shown that Whites also report experiences of discrimination in various domains of life, including housing and work (e.g., Paradies et al, 2015), and that these experiences result in distress (Bower et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Empirical investigations using the RBTSSS, have demonstrated the validity of the scale, as well as found associations between race‐based traumatic stress (RBTS) symptoms and both cultural and psychological variables. Carter, Johnson, et al (2017) found that classes (i.e., types) of racism were predictive of RBTS symptoms, specifically avoidant (e.g., being excluded from work‐related social activities) and aversive (e.g., obtaining membership to an organization, then having qualifications questioned) hostile racism. Additionally, in a sample of people of color, Carter, Johnson, et al (2017) found that RBTS symptoms were positively associated with psychological distress.…”
mentioning
confidence: 99%
See 2 more Smart Citations